Hakikat Belajar Dan Pembelajaran Dalam Penerapan Strategi Pembelajaran Dalam Konsep Islam - Sonya Putri Nelta; Ashavira Julian Dias; Husniah Hasan; Gusmaneli (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The nature of learning and learning in the context of implementing learning strategies in Islamic concepts. Through the Islamic approach, studying and learning is considered a spiritual process that involves knowledge, morals and charity. In this context, learning strategies must include aspects such as spiritual awareness, character formation, and the integration of Islamic values in the curriculum. This research aims to explore how Islamic approaches can be applied in learning to create an environment that promotes deep understanding, active involvement, and holistic self-development.